Recommended remediation strategies for developing core content and skills in primary mathematics: Infant two – Standard five - Trinidad and Tobago. Ministry of Education, Curriculum Planning and Development Division, Mathematics Unit (Mathematics Unit, Curriculum Planning and Development Division, Ministry of Education, GOVTT, 2021)
The Recommended Remediation Strategies for developing Core Content and Skills in Primary Mathematics: INFANT TWO – STANDARD FIVE document has been produced to provide support for teachers and parents to build concepts and skills in students, to mitigate learning loss due to the COVID 19 Pandemic. Diagnostic tests based on the four content strands; number, measurement, geometry, and statistics as identified in the Primary Curriculum were constructed and administered to all students in classes from Infant II to Standard Five in all Government and Government Assisted Primary Schools. A response to the findings from these tests is a set of recommended strategies for remediation classified into three levels based on the number of correct items, per strand. The strand specific classification of bands of performance by levels is included in this document in Appendix 1. Three levels of students’ performances were addressed in each strand: Level I, Level 2, and Level 3. Level 1 recommendations address very little or no understanding of content in the respective strands, Level 2 recommendations address minimum to average understanding of content in the respective strands, and Level 3 recommendations address above average understanding of content in the respective strands.
Keywords: remediation strategies; primary school; mathematics; learning loss; COVID-19; pandemic